Turmoil in Latin America and the Caribbean - Perry, Guillermo E. (Washington, DC: World Bank, 2013)
In this note work from the end of 2001 to August 2002 is updated in an attempt to disentangle potential contagion and spillover effects of the Argentine crisis from other sources of co-movement or market volatility. We also examine the evidence on FDI flows, inquiring about potentially more lasting deterioration of capital flows to the Region. The recent increase in spreads across the region appears more correlated with the largely autonomous increase in spreads in Brazil (caused mostly by uncertainties arising from the electoral period, though also influenced by U.S. stock market turmoil and a fall in exports due to the collapse of the Argentine market) than with the protracted Argentine crisis. To some extent, it reflects some extent general market volatility, which was felt beyond the LAC region. Thus, we may expect that the present situation of high levels and volatility of spreads in the region will be maintained as long as the uncertainties arising from the Brazilian electoral process continue to impact the perception of Brazil country risk; and a further deterioration in this perception might have important consequences on market access and spreads across the region. Political events in other countries (electoral transitions in Bolivia, Colombia, and Argentina, social turmoil in Peru and Venezuela, increased violence in Colombia) as well as some forms of political contagion (Duhalde's statements on the failure of promarket policies in Mercosur; emerging anti-privatization stances in some countries, such as Peru) may have also contributed to spread increases and volatilities. Volatility and increases in risk perception in OECD markets, as a consequence of recent corporate accounting scandals, might also contribute to volatility and high spreads in the region. However, evidence of such effects is so far significant only for a few countries (notably Mexico and Brazil).